2020
DOI: 10.3390/d12020068
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Free-Range Pig Genetic Resources in Southern Africa: Progress and Prospects

Abstract: Pig genetic resources in Africa originate from different regions and were introduced through several migration pathways. Genetic analysis has shown a strong phylogeographic pattern, with pigs on the eastern parts showing a high frequency of alleles from the Far East while the ones on the western parts show a strong European influence. This highlights the influence of trade routes on the genetic legacy of African pigs. They have, however, since adapted to the local environments to produce unique populations wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Pigs have a long history in Africa and the importance of conserving hardy local breeds that can produce pork under less-than-optimal conditions of management and nutrition is increasingly recognized (Darfour-Oduro et al, 2009;Halimani et al, 2010Halimani et al, , 2013Halimani et al, , 2020Kiendrebeogo et al, 2012;Madzimure et al, 2013;Nsoso et al, 2006).…”
Section: Where Are We Going?mentioning
confidence: 99%
See 1 more Smart Citation
“…Pigs have a long history in Africa and the importance of conserving hardy local breeds that can produce pork under less-than-optimal conditions of management and nutrition is increasingly recognized (Darfour-Oduro et al, 2009;Halimani et al, 2010Halimani et al, , 2013Halimani et al, , 2020Kiendrebeogo et al, 2012;Madzimure et al, 2013;Nsoso et al, 2006).…”
Section: Where Are We Going?mentioning
confidence: 99%
“…Pigs have a long history in Africa and the importance of conserving hardy local breeds that can produce pork under less‐than‐optimal conditions of management and nutrition is increasingly recognized (Darfour‐Oduro et al., 2009; Halimani et al., 2010, 2013, 2020; Kiendrebeogo et al., 2012; Madzimure et al., 2013; Nsoso et al., 2006). While modern, high‐producing breeds are used for commercial production, smallholder farmers who cannot afford commercial rations and may not have access to unlimited supplies of water need more forgiving breeds that can nevertheless provide them with a good income (Chiduwa et al., 2008; Madzimure et al., 2013; Mashatise et al., 2005).…”
Section: Where Are We Going?mentioning
confidence: 99%
“…Ouma et al (2015) contended that regardless of who heads a household, it is widely agreed that women and children actively participate in managing pigs and other small animals that are reared in homesteads. Previous studies reported that pig ownership was inclusive of all genders, with a slightly higher number of female owners of locally adopted ones (Morison et al, 2019;Halimani et al, 2020) while males dominate ownership of exotic breeds and their crosses and with large numbers. The dominance of female owners and the spread of pigs within the gender is based on family connections where family members provide assistance in the care of pigs under the supervision of females who are always around home compared to the males (Halimani et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Documenting and monitoring the status of animal genetic resources is one of the vital factors for their sustainable use, development, and conservation (FAO 2011, Cao et al 2021. Indigenous Tswana pigs, just like other indigenous livestock species, are not highly regarded in commercial production system (Halimani 2020). The main reason for that is the slow growth rate compared to the exotic commercial pigs (Wang et al 2021).…”
mentioning
confidence: 99%